Fibre coupled micro-light emitting diode array light source with integrated band-pass filter for fluorescence detection in miniaturised analytical systems - Vaculovičová, Markéta; Akther, Mahbub; Maaskant, Pleun; Brabazon, Dermot; Macka, Mirek (Analytica chimica acta, 2015)
In this work, a new type of miniaturized fibre-coupled solid-state light source is demonstrated as an excitation source for fluorescence detection in capillary electrophoresis. It is based on a parabolically shaped micro-light emitting diode (μ-LED) array with a custom band-pass optical interference filter (IF) deposited at the back of the LED substrate. The GaN μ-LED array consisted of 270 individual μ-LED elements with a peak emission at 470 nm, each about 14 μm in diameter and operated as a single unit. Light was extracted through the transparent substrate material, and coupled to an optical fibre (OF, 400 μm in diameter, numerical aperture NA=0.37), to form an integrated μ-LED-IF-OF light source component. This packaged μ-LED-IF-OF light source emitted approximately 225 μW of optical power at a bias current of 20 mA. The bandpass IF filter was designed to reduce undesirable LED light emissions in the wavelength range above 490 nm. Devices with and without IF were compared in terms of the optical power output, spectral characteristics as well as LOD values. While the IF consisted of only 7.5 pairs (15 layers) of SiO2/HfO2 layers, it resulted in an improvement of the baseline noise as well as the detection limit measured using fluorescein as test analyte, both by approximately one order of magnitude, with a LOD of 1×10(-8) mol L(-1) obtained under optimised conditions. The μ-LED-IF-OF light source was then demonstrated for use in capillary electrophoresis with fluorimetric detection. The limits of detection obtained by this device were compared to those obtained with a commercial fibre coupled LED device.
Keywords: Capillary electrophoresis; Separations; Micro-light emitting diode array; Light source; Optical fibre; Fluorescence detection